Estimation of Soil Moisture Regime Based on Analysis of Rainfall, Air Temperature, and Landform - Soil (Case Study on River Regional Unit (SWS) Pemali - Comal) - Sartohadi, Junun; Saragih, Junita (Forum Geografi, 2004)
The objectives of this research were 1) to determine soil moisture regime based on rainfall and temperature data; 2) to make a correction of the first objective based on soil moisture surplus and deficit calulation; 3) to study the pattern of soil moisture regime distribution in the research area. The field sampling tehniques applied in this research was stratified proposed sampling. Landform unit was applied as strata. Soil depth and texture were considered during field soil sampling within the landform unit. Rainfall and air temperature data were analyzed using Newball Simulation Model (NSM) to determine a tentative soil moisture regime. The tentative soil moisture regime was corrected using calculation soil moisture regime of soil moisture surplus and deficit. The soil moisture surplus and deficit was calculated based on soil depth, soil texture, rainfall, and temperature data. The result of this research were 1) soil moisture regime estimated using NSM ranged from ustic to udic; 2) soil moisture regime corrected using surplus and/ or defiit alulation of soil moisture ranged from xeric to udic; 3) the pattern of soil moisture regime distribution in the reaserch area was not only controlled by the pattern of rainfall â air temperature distribution but it was also controlled by the pattern of soil â landform distribution. Under the some amount of annual rainfall, shallow and coarse texture soils have drier soil moisture regime than deep and fine texture soils.